2019
DOI: 10.1186/s13287-019-1189-x
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of bone marrow-derived mesenchymal stromal cells in the acute lung injury induced by sulfur mustard

Abstract: BackgroundSulfur mustard (SM) is a notorious chemical warfare agent that can cause severe acute lung injury (ALI), in addition to other lesions. Currently, effective medical countermeasures for SM are lacking. Bone marrow-derived mesenchymal stromal cells (BMSCs) possess self-renewal and multipotent differentiation capacity. BMSCs can also migrate to inflammation and injury sites and exert anti-inflammatory and tissue repair functions. Here, we report the curative effect of BMSCs on SM-induced ALI in a mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…Consistent with our results, previous studies demonstrated that intrathecal delivery of BMSCs can relieve neuropathic pain and that the analgesic effect of BMSCs persists for at least 14 days [34,35]. Mesenchymal stem-cell therapy, such as BMSCs treatment, has been considered a potentially successful approach for treating various diseases including neuropathic pain [37,46], spinal cord injury [47,48], Alzheimer's disease [49,50], stroke [51,52], and lung injury [53,54]. BMSCs were the earliest and the most widely studied MSCs in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, previous studies demonstrated that intrathecal delivery of BMSCs can relieve neuropathic pain and that the analgesic effect of BMSCs persists for at least 14 days [34,35]. Mesenchymal stem-cell therapy, such as BMSCs treatment, has been considered a potentially successful approach for treating various diseases including neuropathic pain [37,46], spinal cord injury [47,48], Alzheimer's disease [49,50], stroke [51,52], and lung injury [53,54]. BMSCs were the earliest and the most widely studied MSCs in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…In an in vivo experiment with ALI, we compared the liraglutide alone, three MSCs alone, and combination of liraglutide to observe their repair function. In previous studies, MSCs have been shown to repair ALI [13][14][15][16]19], and liraglutide could alleviate the inflammatory environment of ALI [27][28][29]. In our study, by measuring total protein concentration and cell counts in BALF, wet-to-dry ratio, H&E staining, and lung injury scores, we conclude that liraglutide or MSCs alone and combination of liraglutide could ameliorate the symptoms of ALI.…”
Section: Discussionsupporting
confidence: 69%
“…They secrete paracrine factors that regulate lung endothelial and epithelial permeability, including growth factors, antimicrobial peptides, and anti-inflammatory cytokines, which could alleviate damaged alveolar fluid clearance, improve lung permeability, and mitigate inflammatory disorders [14][15][16][17][18]. In addition, MSCs are widely available and can be collected from the bone marrow [19], adipose tissues [20], placenta [21], umbilical cord [22], and other tissues [23,24]. However, inflammatory stimulation in the ALI lung microenvironment could lead to a decrease in MSC survival and weaken paracrine capacity [24].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study demonstrated that pMScs could inhibit the inflammatory response of LPS-induced RAW264.7 macrophage inflammatory model in vitro. in accordance with other previous studies (42)(43)(44), the nc, lPS and lPS + pMSc groups were used both in vitro and in vivo. The effects of pMSc administration without lPS stimulation have not been evaluated in the present study.…”
Section: Discussionmentioning
confidence: 94%